Annotated catalogue of Australian weevils (Coleoptera: Curculionoidea) - Pullen, Kimberi R.; Jennings, Debbie; Oberprieler, Rolf G. (Zootaxa, 2014)
This catalogue presents the first-ever complete inventory of all described taxa of Australian weevils, including both valid and invalid names. The geographical scope spans mainland Australia and its continental islands as well as the subantarctic Heard and McDonald Islands, the Pacific Lord Howe and Norfolk Islands and the Indian-Ocean Christmas Island. 4111 species in 832 genera (including one extinct species and one fossil) are recognised as occurring in this territory, distributed over seven families, 20 subfamilies and 94 tribes. The families and subfamilies are arranged in a currently accepted phylogenetic sequence but the tribes, genera and species in alphabetical order. Introductory chapters outline the discovery and composition of the Australian weevil fauna, the burden of synonymy, the format and conventions of the catalogue and the taxonomic and nomenclatural changes proposed. Sixteen new genera and six new species are described, two new names and 25 new generic and 72 new species synonymies and 189 new combinations are proposed and 46 type species designations are effected. The records of 356 taxa are annotated to justify or explain various taxonomic and nomenclatural acts and issues, covering descriptions of new taxa, new synonymies and generic combinations, artificial taxon concepts, changes in classification and a number of nomenclatural matters. The catalogue of the taxa present in Australia is followed by a list of 19 species incorrectly recorded from Australia or introduced as biocontrol agents but not established, and by one species inquirenda. All these records are also annotated. Two appendices list the 102 species introduced into Australia, both accidental and deliberate (as weed control agents). A bibliography with full references of all original descriptions and pertinent other citations from the literature is provided, and an index to all names concludes the catalogue.